Demographic characteristics of ethical consumers - Schnitz, Casey Lee (Kansas State University, 2008)
Changes in consumer preferences have frequently created markets for new products. Recently these changes in consumer preferences have been brought on by people we term as "ethical consumers." These consumers demand is driven by the extrinsic characteristics of the products they purchase. In this thesis we analyze consumer demand theory for its application to ethical consumers, we determine the demographic factors that influence the emergence of the ethical consumer, and we classify ethical consumers by the categories of extrinsic factors influencing their consumption decisions. We explore the theory of Abraham Maslow's Hierarchy of Needs. Our theory tells us that as people reach the self-actualizing stage in Maslow's Hierarchy they have the income and education to make their purchase decisions based on how it will effect others and the environment. We found higher income levels and educational attainment to be characteristics of our ethical consumer. We also found that the reasons these ethical consumers are purchasing ethical products fall into five categories, environment, social justice, biodiversity, and religious. This paper develops a theory on Ethical consumers, determining the demographics of the consumer and their motivations for their ethical purchases. Future research may look at using this information to create a demand theory for ethical consumers.
Keywords: ethical cosumers; demographics; organic; food consumption; Agriculture, Food Science and Technology (0359)